2009
DOI: 10.1042/bj20090613
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα1 regulates the antioxidant status of vascular endothelial cells

Abstract: AMPK (AMP-activated protein kinase) is a key regulator of cellular energy because of its capacity to detect changes in the concentration of AMP. Recent evidence, however, indicates the existence of alternative mechanisms of activation of this protein. Mitochondrial ROS (reactive oxygen species), generated as a result of the interaction between nitric oxide and mitochondrial cytochrome c oxidase, activate AMPKalpha1 in HUVECs (human umbilical-vein endothelial cells) at a low oxygen concentration (i.e. 3%). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 31 publications
9
144
0
Order By: Relevance
“…AMPKa1 also regulates oxidative stress by controlling the expression of various genes involved in antioxidant defense such as manganese superoxide dismutase, g-glutamylcysteine synthase, and thioredoxin in endothelial cells (57). Oxidative stress upregulates the cascade of NF-kB, expression of cell adhesion molecules, and extravasations of mononuclear cells during EAE disease.…”
Section: Discussionmentioning
confidence: 99%
“…AMPKa1 also regulates oxidative stress by controlling the expression of various genes involved in antioxidant defense such as manganese superoxide dismutase, g-glutamylcysteine synthase, and thioredoxin in endothelial cells (57). Oxidative stress upregulates the cascade of NF-kB, expression of cell adhesion molecules, and extravasations of mononuclear cells during EAE disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AMPK signaling (likely via PGC1␣) stimulates the expression of anti-oxidant enzymes (61,62) whereas PI3K/Akt signaling impairs ROS scavenging (63,64). Consistently, we observed that blocking the AMPK pathway largely eliminated the apelin-stimulated expression of anti-oxidant enzymes (catalase, GPx) and apelin-suppressed expression of pro-oxidant enzyme (P47phox subunit of NADPH oxidase) and inhibiting PI3K/Akt led to up-regulation of antioxidant enzymes (SOD1 and catalase) (Fig.…”
Section: Tnf␣-induced Ros Production and Tnf␣-impaired Antioxidant Enmentioning
confidence: 99%
“…39 Moreover, recent evidences indicate the existence of an alternative pathway of AMPK activation, triggered by mitochondrial ROS and involving FoxO3A and its target genes (SOD, catalase, PGC1α). 40 Yet, several questions remain unanswered. Although it is largely accepted that activated AMPK is able to directly phosphorylate FoxO3A, the physiological or patho-physiological stimuli triggering AMPK-dependent FoxO3A phosphorylation still have to be identified and, most importantly, it is not clear yet which FoxO3A functions are actually regulated by these multiple phosphorylations.…”
mentioning
confidence: 99%